2011
DOI: 10.1007/s13142-011-0059-6
|View full text |Cite
|
Sign up to set email alerts
|

Proactive recruitment predicts participant retention to end of treatment in a secondhand smoke reduction trial with low-income maternal smokers

Abstract: Improving smoking intervention trial retention in underserved populations remains a public health priority. Low retention rates undermine clinical advancements that could reduce health disparities. To examine the effects of recruitment strategies on participant retention among 279 low-income, maternal smokers who initiated treatment in a 16-week behavioral counseling trial to reduce child secondhand smoke exposure (SHSe). Participants were recruited using either reactive strategies or methods that included pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
0
19
0
1
Order By: Relevance
“…A recent study found that retention was five times greater for low-income pregnant participants enrolled in a second-hand smoke reduction trial when recruited both reactively and proactively compared to reactively alone. [61] Future research should test the utility of proactive recruitment approaches in the Centrelink setting . This may increase retention rates and engagement with treatment in smokers recruited from Centrelink and similar social welfare agencies internationally.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that retention was five times greater for low-income pregnant participants enrolled in a second-hand smoke reduction trial when recruited both reactively and proactively compared to reactively alone. [61] Future research should test the utility of proactive recruitment approaches in the Centrelink setting . This may increase retention rates and engagement with treatment in smokers recruited from Centrelink and similar social welfare agencies internationally.…”
Section: Discussionmentioning
confidence: 99%
“…Proactive recruitment strategies, that include assessing the risks of smoking with a focus on child health during routine clinic visits and provision of referral information about clinical trials to all identified smokers, may improve recruitment rates among underserved women (Collins et al, 2011). Potentially effective retention strategies for low-income minority women include provision of financial and other incentives, regular updates of contact information, and emphasis on cultural sensitivity of research staff (El-Khorazaty et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…60 Participants were recruited both actively from pediatric primary care and community clinics providing the Special Supplementary Nutrition Program for Women, Infants, and Children (WIC) as well as passively with advertisements in free community newspapers, on mass transit serving low-income neighborhoods, and on fliers in local stores. Participants were randomized with block randomization using small blocks of random length, stratified by child race, gender, and recruitment site (WIC, pediatrics, or advertisements).…”
Section: Methodsmentioning
confidence: 99%